Suspected vagal reflex and hyperkalaemia inducing asystole in an anaesthetised horse. (19th November 2021) - Ryan, Aoife; Gurney, Matthew; Steinbacher, Roswitha
Summary: A 10‐year‐old 466 kg mustang gelding presented to an equine referral hospital for surgical repair of nasal, frontal and lacrimal bone fractures from an unknown trauma. Surgical repair was performed under general anaesthesia, including a right‐sided maxillary regional anaesthetic block with mepivacaine hydrochloride. Progressive hyperkalaemia was documented perianaesthetically (T‐3 mins; 134 mins after induction; potassium 6.4 mmol/L (ref 3.5‐5.1 mmol/L). Perianaesthetic bradycardia was attributed to alpha −2 agonist infusion administration, and other characteristic ECG changes (flattened P waves, narrow T waves of increased amplitude, prolonged QRS complex) were not documented. Asystole occurred 137 min after induction of anaesthesia; however, a review of the available literature suggests the degree of hyperkalaemia documented was unlikely to be the primary cause of asystole but may have been a contributing factor. It is hypothesised that a trigeminocardiac reflex was the primary contributory factor to asystole in the described case, and may represent a maxillomandibulocardiac reflex that has not been previously described in the horse.